Variations in Craniosynostosis Surgery Affect Perioperative Outcomes: An Analysis of Peds-NSQIP Data. Issue 2 (June 2022) - Hopkins, Elizabeth R.; Sanchez, Ruston; Leverson, Glen; Mount, Delora; Garland, Catharine B.
While many single-institution studies have investigated the relationship between surgical technique and perioperative outcomes in craniosynostosis surgery, the Pediatric National Surgical Quality Improvement Program (Peds NSQIP) allows this on a nationwide scale. By analyzing the CPT codes associated with craniosynostosis surgery, insight can be gained not only into the prevalence of certain procedures, but into their effects on perioperative outcomes. Patients with craniosynostosis were selected from the Peds NSQIP database (2012-2018) based on the corresponding ICD-9 code. CPT codes associated with single suturectomy or craniectomy with and without the use of distractors/springs, and craniotomy with and without the use of bone grafts, were used to further identify patient groups. Outcome variables included operative time, hospital stay, and blood transfusions. Analysis showed that patients undergoing single suturectomies or extensive cranioplasties with distractor/spring placement had shorter operative times, shorter hospital stays, and decreased incidence of blood transfusions. The use of bone grafts was associated with significantly longer operative times and a higher incidence of blood transfusions, as well as higher volumes of blood transfused. Distractor/spring use can facilitate shorter operative times and decreased rates of blood transfusion. Bone grafting, while commonly used, is associated with increased rates of blood transfusion. Despite the statistical significance of these results, the nonspecific nature of the craniosynostosis-specific CPT codes severely limited the extent of analysis possible. Updating the CPT coding system would allow for greater utility of NSQIP in determining nationwide procedure-specific outcomes.